For the Love of Sisi: Peer Support and Friendship in Navigating Health Adversity - Velisiwe Gasa; Nomanesi Madikizela-Madiya; Mishack Thiza Gumbo; Meahabo Dinah Magano; Enid Manyaku Pitsoane; Vimbi Petrus Mahlangu; Soul Shava; Khabonina Grace Nkumane; Pertunia Rebotile Machaisa; Thembi Phala; Loyiso Luvalo; Abraham Motlhabane; Sibusiso D. Ntshangase (GHMJ (Global Health Management Journal), 2025)
Health adversity, whether due to chronic illness, disability, or severe medical conditions, often leads to emotional, social, and psychological challenges. While much research has focused on clinical care, growing attention is paid to peer support and friendship as crucial non-clinical resources. The experience of Sisi, a person living through health adversity, offers an illustrative case of how love and social connection can play a transformative role in coping and resilience, even if it is for a short while. This paper explores the importance of peer support and friendship in enhancing empowerment, maintaining personal identity, and encouraging meaning-making during health-related adversity. It seeks to contribute knowledge on how social relationships function as sources of emotional comfort and as mechanisms that enable individuals to reframe their experience and maintain a strong sense of self in times of illness. The narratives show that peer support and friendship are essential facilitators of psychological empowerment, assisting individuals in feeling more in control and competent even in the face of adversity. Relationships with peers protect identity by affirming personal narratives beyond the illness. Furthermore, they act as informal support systems that augment medical interventions, frequently improving quality of life and psychological resilience. Peer connection can assist individuals in viewing illness not merely as a medical experience but as a collective human experience characterized by connection and meaning. The insights underscore the necessity for more comprehensive, person-centered strategies in health care that acknowledge love, friendship, and social connection as vital elements of recovery and resilience.